Hubungan Pola Asuh Demokratis dan Kematangan Emosi dengan Kenakalan Remaja Siswa SMA Al-Islam - Hafida Nur Ifni; Lely Ika Mariyati (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This study aims to determine the relationship between democratic parenting patterns and emotional maturity with juvenile delinquency of Al-Islam High School students, meaning The three variables used in this research are: democratic parenting (X1) and emotional maturity (X2). Juvenile Delinquency Y. Juvenile Delinquency (Y). This research is a correlational quantitative research. The sample in this study was 289 students from 1,035 students as the population at Al-Islam High School. The data collection technique used in this study used a psychological scale with a Likert scale model and documentation. The data collection technique in this study used 3 scales, namely the democratic parenting scale consisting of 2 items that were dropped out of 35 existing Of the 35 existing items, 2 items were declared invalid, so the number of valid items was 33 items with a reliability test showing a Cronbach's Alpha score of 0.943. and emotional maturity consisting of 18 items that were dropped out of 41 existing items, so that the number of valid items was 23 items with a reliability test showing a Cronbach's Alpha score of 0.792. And the juvenile delinquency scale contains 17 items that were dropped from the 37 existing items, so the number of valid items is 20 items with a reliability test showing a Cronbach's Alpha score of 0.836.